Polyoxometalates confined within nanotubes - Jordan, Jack W. (2021)
The work presented in this thesis investigates polyoxometalates (POMs) confined within nanotubes and their structure, host-guest interactions and electrochemical properties. Utilising a suite of spectroscopic and microscopic techniques, the encapsulation of POMs within single walled carbon nanotubes (SWNTs) was revealed to be redox driven, in which spontaneous charge transfer from the SWNTs to POMs in solution gave rise to coulombic attraction between the two species, driving encapsulation of the POMs within the SWNTs. The level of SWNT oxidation was dictated by the energy levels of the corresponding encapsulant POM. In cases where spontaneous electron transfer between the two could not occur, the levels of encapsulation were seemingly lowered. Utilising a range of imaging conditions, transmission electron microscopy (TEM) revealed that the encapsulated POMs were extremely beam sensitive, leading to a rapid decomposition of the native POM@SWNT structure. The high level of encapsulation meant that the reactivity of ~100 molecules could be studied at once, as well as using AC-TEM methods to study the atomic nature of the reaction. Electrochemical analysis of the POM@SWNT materials revealed the electron transfer between the encapsulated POMs and the electrode was rapid during electrochemical charge-discharge, mediated by the intimate electronic contact between the POMs and SWNTs. The SWNTs also served to stabilise the encapsulated POMs, allowing the material to be cycled over 1000 times with minimal changes to the current response, as well as allowing a cyclic voltammogram of the encapsulated POMs to be obtained in an electrolyte with an extremely high pH. When moving from protic electrolytes, the CV responses of the POM@SWNT materials drastically altered due to the inhibited mass transport of larger cations during POM reduction, allowing the POM@SWNT materials to be used as a model system to better understand the mass transport of ions in these nanodomains during electrochemical cycling. By encapsulating POMs within boron nitride nanotubes (BNNTs) the nature of host-guest interactions in these systems could be better understood by probing the vibrational spectra of the guest POMs. Photoluminescence (PL) measurements and low temperature Raman measurements demonstrated that the interaction between the two allowed electronic communication, manifested as quenching of PL emissions and the emergence of new ones at low temperatures.